Stable isotopes (carbon, nitrogen, sulfur), diet, and anthropometry in urban Colombian women: Investigating socioeconomic differences. Issue 2 (12th October 2014) - Bender, Richard L.; Dufour, Darna L.; Valenzuela, Luciano O.; Cerling, Thure E.; Sponheimer, Matt; Reina, Julio C.; Ehleringer, James R.
<x xml:space="preserve">Abstract</x> Objectives We conducted stable isotope and dietary analyses of women from higher and lower socioeconomic status (SES) groups in Cali, Colombia. The objectives were to test between‐group differences in stable isotope, dietary, and anthropometric characteristics, and to evaluate relationships between diet and stable isotope values. Methods Hair samples from 38 women (mean age 33.4) from higher and lower SES groups were analyzed for δ13C, δ15N, and δ34S values. Dietary intake was assessed via 24‐h recalls. Anthropometric variables measured were body mass index, five body circumferences, and six skinfold thicknesses. Results Mean δ13C and δ15N values of the higher SES group (−16.4 and 10.3‰) were significantly greater than those of the lower SES group (−17.2 and 9.6‰; P < 0.01), but mean δ34S values did not differ significantly between groups (higher SES: 4.6‰; lower SES: 5.1‰). The higher SES group consumed a greater percentage of protein than the lower SES group (14% vs. 12% of energy; P = 0.03), but the groups did not differ in other dietary characteristics or in anthropometric characteristics. δ13C, δ15N, and δ34S values were not correlated with intake of the dietary items predicted (sugars, animal‐source protein, and marine foods, respectively). The lower SES group was more variable in all three stable isotope values (P < 0.05), mirroring a trend toward greater dietary variability in this group. Conclusions Stable isotope values revealed a difference between SES groups that was not explained by the dietary data. The relationship between diet and stable isotope composition is complex. Am. J. Hum. Biol. 27:207–218, 2015. © 2014 Wiley Periodicals, Inc.